Several genotypes, one phenotype: PIK3CA/AKT1 mutation-negative hidradenoma papilliferum show genetic lesions in other components of the signalling network - Pfarr, Nicole; Allgäuer, Michael; Weichert, Wilko; Schirmacher, Peter; Stenzinger, Albrecht (Pathology, 2019)
Summary - About 60-70% of hidradenoma papilliferum (HP), a benign tumour of the anogenital region, were recently described to harbour mutations in major driver genes of the PI3K/AKT/MAPK-signalling pathways. However, the underlying genetic defects of the non-mutant cases are still unknown. Using a 409 gene panel, we employed targeted next generation sequencing to investigate the mutational landscape in a cohort of seven PI3K/AKT-negative cases and five cases with known hotspot mutations in either PIK3CA or AKT1. In total, we identified 29 mutations in 22 of 409 genes. The four cases with PIK3CA hotspot mutations carried no or only few additional mutations. The AKT1 hotspot mutated case harboured additional mutations in four genes (SYNE1, ADAMTS20, EP400 and CASC5). At least two of these genes are involved in or contribute to the PI3K/AKT-pathway. In the seven non-hotspot mutated cases we observed 18 mutations. Each case carried at least one mutation in a gene contributing to or involved in PI3K/AKT-signalling. Affected genes were PIK3CA (n=1, non-hotspot mutation), PIK3R1 (n=3), SYNE1, AR, IL6ST, PDGFRB, KMT2C, AR, BTK, DST, KAT6A, BRD3, RNF213, USP9X, ADGRB3, MAGI1, and IL7R (each gene mutated once). The identified PIK3CA and PIK3R1 mutations lead to constitutive activated PI3K/AKT-signalling. In conclusion, we demonstrate the genetic basis of HP in all cases. Our data suggest that tumourigenic alterations in the PI3K/AKT-pathway are indispensable in HP and establish a homogenous morphomolecular entity with a functionally converging and selecting tumourigenic mechanism.
Gesehen am 27.06.2019